SPIRITUAL KNIGHT MISSION IN NOVEL ASMARA DJIBRAT LUDIRA - Ibrahim, Fahmi Iqbal; Darmoko, Darmoko (UI Scholars Hub, 2020)
One result of culture is literary work, but broadly speaking literature is the work of individuals, only the object delivered will not be separated from the culture and social life of the community. The close relationship between literature and culture can produce literary works that have a function as cultural preservation. A complex culture can be reflected in a literary work. If traced carefully, it can be known that some authors have included a tradition and culture of an area in their literary work. One type of imaginary story is a novel. A novel is a term for a long, imaginary literary work that presents characters and displays a series of events and settings in a structured manner. This study uses the novel Asmara Djibrat Ludira (Furthermore abbreviated ADL) as a data source. The theory used for structural analysis in the form of figures, characterizations, plot, background, themes, and message in ADL novels is a structural theory from Panuti Sudjiman a book called “Memahami Cerita Rekaan” (Understanding Fiction Stories), while for analyzing darma (spiritual mission) in Javanese morality context, researcher using ethical theory from Franz Magnis Suseno and descriptive - qualitative method from Teeuw and John W. Creswell. The conclusion of this study shows that moral message contained in it regarding the role of soldiers who must always hold fast to the principles of spiritual mission and the spiritual mission (darma) of the main character's knights is done by fighting the invaders and saving his lover.